Estudantes com deficiência no ensino superior: acessibilidade e inclusão na Universidade Federal do Tocantins, Câmpus de Arraias - Souza, Raquel Nascimento de (Universidade Federal do Tocantins, 2024)
The inclusion of students with disabilities in educational spaces has broadened the spectrum of opportunities for these people to participate in university spaces. This study discusses the access and permanence policies offered by the Federal University of Tocantins for the full participation of people with disabilities in this educational context. Its aim was to understand the access and permanence policies implemented by the Federal University of Tocantins and the perceptions of students with disabilities enrolled at the Professor Dr. Sérgio Jacintho Leonor campus in Arraias - TO. From this perspective, the theoretical underpinning is based on studies in relation to special and inclusive education in accordance with Brazilian and international legislation, as well as studies by Mazzotta, Chahini and Zardo. To this end, we conducted a qualitative, descriptive-exploratory study. The methodological procedures were based on a bibliographic and documentary review of research dealing with special education and its implementation, as well as legislation and regulations governing inclusion, accessibility, guaranteed access, permanence and completion of higher education courses. During the period in which social distancing was determined due to the pandemic caused by COVID-19, we conducted individual interviews virtually with open-ended questions and dialogues with five students with disabilities from the face-to-face undergraduate courses offered by the Federal University of Tocantins, Arraias campus, enrolled between 2018 and 2021. The students' reports make up the corpus of this research, along with institutional documents, resolutions and UFT reports published between 2018 and 2021. The data was analyzed using the assumptions of Bardin's Content Analysis approach and was organized into three thematic categories, namely: 1) Access and entry policies at UFT; and 2) Institutional planning for conditions of permanence; and 3) Conditions of permanence for students with disabilities at UFT. The first category looked at the selection processes for admission to the face-to-face undergraduate courses offered at the Arraias campus, specifically at how the current legislation is implemented in these notices, guaranteeing the reservation of places for people with disabilities in Higher Education; and what inclusion actions for access and admission of people with disabilities the UFT has provided for in its institutional planning. The second category presented an analysis of UFT's institutional planning on what has been offered or proposed for the permanence and success of students with disabilities, guaranteeing an equitable education with accessibility conditions through the analysis of the Institutional Development Plans (PDI) 2016-2020 and 2021-2025 and the Arraias Campus Development Plan (PDC). In the third category, inferences and interpretations were made about students' perceptions of the conditions of permanence and the barriers encountered in their training process based on the seven dimensions of accessibility proposed by Sassaki and the barriers conceptualized in the Brazilian Inclusion Law (LBI). The results show that UFT has presented inclusion and accessibility actions and targets in its Institutional Development Plans, however, in the academic community's evaluation reports, one of the worst points has been accessibility. We point to the need to create an accessibility center that is part of the institution's administrative sphere, contributing to the creation and development of policies, assistance and actions; hiring specific and specialized professionals and composing a multi-professional team at the Arraias campus to assist students; expanding welcoming and pedagogical follow-up actions; curricular and assessment adaptations; teacher training and awareness-raising to eliminate attitudinal and pedagogical barriers; expansion of permanence policies through actions beyond just offering financial aid; translation and interpretation of public notices and admission documents into Libras; and breaking down accessibility barriers presented in the LBI. The conclusion is that UFT's documents have sought to meet the legal requirements for access and permanence, but that there is a need to implement inclusive policies and actions in teaching, research and extension.